1999
DOI: 10.1093/jac/43.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-resistant TEM  -lactamases: phenotypic, genetic and biochemical characteristics

Abstract: Beta-lactamases represent the main mechanism of bacterial resistance to beta-lactam antibiotics. The recent emergence of bacterial strains producing inhibitor-resistant TEM (IRT) enzymes could be related to the frequent use of beta-lactamase inhibitors such as clavulanic acid, sulbactam and tazobactam in hospitals and in general practice. The IRT beta-lactamases differ from the parental enzymes TEM-1 or TEM-2 by one, two or three amino acid substitutions at different locations. This paper reviews the phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
170
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(177 citation statements)
references
References 57 publications
5
170
0
1
Order By: Relevance
“…Previous studies with various TEM-1 Arg244 mutants have shown a similar effect upon K m with penicillin substrates. 28,29 The K m values for cephalothin and cephalosporin C were too high to be reliably determined and so the relative contribution of K m and k cat upon catalytic efficiency of TEM-1 Arg244Ala is unknown for these substrates. However, the catalytic efficiency of the Arg244Ala enzyme, relative to wild-type TEM-1, was reduced >1000-fold for the cephalothin and cephalosporin C substrates (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with various TEM-1 Arg244 mutants have shown a similar effect upon K m with penicillin substrates. 28,29 The K m values for cephalothin and cephalosporin C were too high to be reliably determined and so the relative contribution of K m and k cat upon catalytic efficiency of TEM-1 Arg244Ala is unknown for these substrates. However, the catalytic efficiency of the Arg244Ala enzyme, relative to wild-type TEM-1, was reduced >1000-fold for the cephalothin and cephalosporin C substrates (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…IRT-producing mutants have been reported in both general practice and hospitals. 10,11 Nosocomial outbreaks of Klebsiella spp. resistant to the third-generation cephalosporins due to the production of ESBL have been reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because expression of resistance is affected by multiple factors, the same ESBL can produce different resistance phenotypes, depending on the bacterial carrier and test conditions (17,23). There are also increasing reports of more-complex ESBL phenotypes that include additional mechanisms of resistance, such as AmpC-type enzyme production (both chromosomal and plasmid-mediated), TEM and SHV beta-lactamases with reduced affinities for beta-lactamase inhibitors, hyperproduction of penicillinase, and porin changes (4,6,8,17,23,26,32,34,39,49,(52)(53)(54).…”
mentioning
confidence: 99%